TAX AND SOCIETY RESPONSIBILITIES: PURPOSE A TAX RETURN PROGRAM TO COMBINATE THE CHAIN - Andi Andi (CV. Adiba Aisha Amira, 2025)
The study explores the impact of tax cuts designed to support vulnerable communities as an attempt to empower and improve social well-being. With a focus on tax cutting policies as a tool to reduce socio-economic inequalities, the study identifies how tax reductions can contribute to improving the economic conditions of individuals and families in vulnerable groups, as well as their impact on the economy as a whole. Through analysis of literature and empirical survey data, the study found that tax cuts programmes have significant potential in increasing purchasing power, stimulating small investments, and reducing poverty and economic inequality. However, the effectiveness of the program depends heavily on proper design, implementation, and monitoring to avoid abuse and ensure that benefits are directed to those who really need it. The study also highlights the importance of considering the fiscal impact of tax cuts and the need to integrate them into broader economic and social development strategies. The findings from this study provide insight into how tax policies can be used to empower people and make recommendations for more responsive and inclusive tax policy formulation in the future.